THE EFFECT OF WORK LIFE BALANCE, JOB SATISFACTION, AND WORK FATIGUE ON THE PERFORMANCE OF GENERATION Z EMPLOYEES IN THE FOOD AND BEVERAGE SECTOR IN CIREBON CITY - Zainab, Siti; Listianty, Diva; Ardiansyah, Andhika; Brilyanto, Angga Prayogi (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
This study explores how work-life balance, job satisfaction, and work fatigue influence the performance of Generation Z employees in Cirebon City's food and beverage industry. Known for valuing flexibility, mental health, and personal fulfillment, Generation Z tends to be highly responsive to organizational factors that impact their work outcomes. Using a quantitative method, data were gathered through online questionnaires and analyzed with the Structural Equation Modeling approach based on Partial Least Squares (SEM-PLS). The findings reveal that both work-life balance and job satisfaction have been proven to make a significant and strong contribution to shaping employee performance, while work fatigue exerts a significant negative influence. These results underscore the importance of organizational support in creating a balanced and satisfying work environment, as well as in minimizing fatigue, which is crucial for companies seeking to improve productivity, reduce turnover, and attract younger talent to demanding sectors like food and beverage.